POWER-PLANT VIBROACOUSTICS IMPACT ON NOISE LEVELS IN FLOATING CRANE CABINS - Elena V. Yegelskaya (Advanced Engineering Research, 2012)
The experimental results of th e noise spectra in the floating crane cabins under the sound radiation of the IC e ngine power - plant are presented. The frequency ranges when noise levels in the cabins exceed the sanitary norms are shown.